Accelerated Discovery and Design of Ultralow Lattice Thermal Conductivity Materials Using Chemical Bonding Principles. (17th December 2021) - He, Jiangang; Xia, Yi; Lin, Wenwen; Pal, Koushik; Zhu, Yizhou; Kanatzidis, Mercouri G.; Wolverton, Chris
Abstract: Semiconductors with very low lattice thermal conductivities are highly desired for applications relevant to thermal energy conversion and management, such as thermoelectrics and thermal barrier coatings. Although the crystal structure and chemical bonding are known to play vital roles in shaping heat transfer behavior, material design approaches of lowering lattice thermal conductivity using chemical bonding principles are uncommon. In this work, an effective strategy of weakening interatomic interactions and therefore suppressing lattice thermal conductivity based on chemical bonding principles is presented and a high‐efficiency approach of discovering low κL materials by screening the local coordination environments of crystalline compounds is developed. The resulting first‐principles calculations uncover 30 hitherto unexplored compounds with (ultra)low lattice thermal conductivities from 13 prototype crystal structures contained in the Inorganic Crystal Structure Database. Furthermore, an approach of rationally designing high‐performance thermoelectrics is demonstrated by additionally incorporating cations with stereochemically active lone‐pair electrons. These results not only provide atomic‐level insights into the physical origin of the low lattice thermal conductivity in a large family of copper/silver‐based compounds but also offer an efficient approach to discover and design materials with targeted thermal transport properties. Abstract : A strategy for suppressing lattice thermal conductivity based on chemical bonding principles is developed. The filling of the p‐d antibonding states formed between Cu/Ag‐ d and anion‐ p and edge/face‐sharing polyhedra jointly weaken chemical bonds and lead to low lattice thermal conductivity. A fast screening based on local coordination environments and first‐principles calculations uncovers 30 new compounds with ultralow lattice thermal conductivities.